A comprehensive model for assessing water engineering facilities heritage in grand canal’s huitong river during the ming and qing dynasties - Lifeng Tan; Xin Qiu; Cheng Wang; Zhichao Sun; Xiaohui Hou; Jiabao Qiao; Chen Yang; Jingyi Xin (Scientific Reports)
Abstract The Beijing-Hangzhou Grand Canal, as the longest artificial waterway in the world, preserves a significant number of water engineering facilities along its route. During the Ming and Qing dynasties, water transport of grain peaked, and these facilities played a crucial role in water resource management and navigation. To protect the historical value of the facilities, constructing a water engineering facility importance assessment model is crucial.In this study, the water engineering facilities in the Huitong River section were selected. Their Ming—Qing relationship network was built using UCINET6.769, and key indexes such as betweenness centrality were extracted for importance analysis. This study innovatively combines SNA, kernel density, and TOPSIS to build a comprehensive assessment system, first applied to cultural heritage protection, bringing new vitality to the field. The results indicate that compared to the Ming dynasty, the overall network scale of water engineering facilities in the Huitong River section expanded and became more dispersed during the Qing dynasty. Key facilities were primarily concentrated in the Northern Five Lakes and Nanyang Lake regions. Ultimately, the study produced a comprehensive ranking of the significance of water engineering facilities for both dynasties, revealing that the core facilities increased from 19 in the Ming dynasty to 31 in the Qing dynasty.